ANALISIS KEMAMPUAN LITERASI MATEMATIS SISWA KELAS IX PADA MATERI BANGUN RUANG SISI LENGKUNG - Nina Ainur Rohmah; tika septia; Rahma Wahyu (Program Studi Tadris Matematika Fakultas Tarbiyah Institut Agama Islam Al-Qolam Malang, 2024)
Currently learning is increasing including learning mathematics. In learning mathematics students are required not only to be able to count, but also to be able to solve problems, especially in everyday life. The purpose of this study was to analyze the mathematical literacy abilities of class IX students. The research method used is descriptive with a qualitative approach. The subject of this study consisted of 4 students who were randomly selected. Based on the results of the study, the subject experienced a little difficulty in solving the problem, the subject needed quite a long time to be able to reason the problem into everyday problems. From this it can be concluded that students' mathematical abilities are still weak because they still experience difficulties in solving math problems using the HOTS model questions on curved side shapes